Hyponatremia in ultradistance triathletes - Speedy, D. B.; Noakes, T. D.; Rogers, I. R.; Thompson, J. M.; Campbell, R. G.; Kuttner, J. A.; Boswell, D. R.; Wrigth, S.; Hamlin,M. (Medicine & Science in Sports & Exercise, 1999)
Referat siehe MF 164961.